2023
DOI: 10.1007/s00296-023-05358-7
|View full text |Cite
|
Sign up to set email alerts
|

Balneotherapy for osteoarthritis: a systematic review

Abstract: This systematic review is aimed to evaluate the effects of balneotherapy with thermal mineral water for managing the symptoms and signs of osteoarthritis located at any anatomical site. The systematic review was conducted according to the PRISMA Statement. The following databases were consulted: PubMed, Scopus, Web of Science, Cochrane Library, DOAJ and PEDro. We included clinical trials evaluating the effects of balneotherapy as a treatment for patients with osteoarthritis, published in English and Italian la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Water-based rehabilitation is a widely employed approach for the prevention and management of numerous conditions [ 14 , 103 , 111 , 122 , 151 ]. In the field of musculoskeletal conditions, water-based exercise has been utilized to enhance pain management and functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Water-based rehabilitation is a widely employed approach for the prevention and management of numerous conditions [ 14 , 103 , 111 , 122 , 151 ]. In the field of musculoskeletal conditions, water-based exercise has been utilized to enhance pain management and functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, pain and quality of life were the primary symptoms assessed, and both demonstrated improvement following treatment with thermal mineral-rich water in all the included studies. Nevertheless, it is important to note that the quality of several studies was deemed suboptimal, highlighting the need for further clinical trials in this field [ 103 ].…”
Section: Spa Therapy Effects On Frailty In Rheumatic Diseases: Clinic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, this kind of study is difficult to standardize [ 33 ]. Thus, according to several systematic reviews evaluating nonpharmacological treatment [ 34 , 35 , 36 , 37 ], the CLEAR NPT checklist was used [ 33 ]. This checklist contains 10 parameters, and for each item the choice was between “Yes”, “No” or “Unclear”.…”
Section: Methodsmentioning
confidence: 99%
“…One study found that people with osteoarthritis experienced a significant reduction in pain and stiffness and improved function when they underwent balneotherapy and pelotherapy and consumed water compared with untreated patients [ 185 ]. Another study showed that patients with knee osteoarthritis who drank sulfur-containing water for four weeks experienced a significant decrease in pain and an improvement in function compared with those who drank tap water [ 186 ].…”
Section: Role Of Hydrogen Sulfidementioning
confidence: 99%